Engineered MoS2 nanostructures via ultrasonic liquid-phase exfoliation: morphological diversity for enhanced electrochemical applications - Sayma Adriana Rodríguez-Montelongo; Felipe de Jesús Barraza-García; Brenda Irais Orea-Calderón; Florentino López-Urías; Emilio Muñoz-Sandoval (Materials Research Express)
The advancement of two-dimensional (2D) materials, particularly molybdenum disulfide (MoS _2 ), has garnered substantial interest owing to their exceptional properties and potential applications in electronics, energy storage, catalysis, and sensing. This study explored the electrochemical properties of MoS _2 nanostructures synthesized via ultrasonic-assisted liquid-phase exfoliation, using N, N-dimethylformamide (DMF) as the liquid medium. The synthesis yielded diverse morphologies, including few-layer nanosheets, needle-like tubular structures, and fullerene-like morphologies (FLM). The emergence of FLM was associated with sulfur vacancies, likely filled with carbon or nitrogen atoms from the decomposition of DMF. Structural and compositional characterizations were performed using x-ray diffraction (XRD), Raman spectroscopy, and morphological analysis. Cyclic voltammetry (CV) was performed to evaluate the electrochemical behavior. XRD confirmed a hexagonal crystalline structure, whereas Raman spectroscopy validated the few-layer nature of MoS _2 . CV analysis highlighted pronounced faradaic contributions at the reactive edge sites and molybdenum reduction processes, which enhanced the charge storage performance of the material. These results demonstrate a scalable synthesis approach for MoS _2 nanostructures with tunable morphologies and improved electrochemical characteristics, offering significant potential for advanced energy storage applications.